2010
DOI: 10.1016/j.neuron.2010.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of a Neural Network for Aversive Olfactory Learning in Caenorhabditis elegans

Abstract: SUMMARY Many animals use their olfactory systems to learn to avoid dangers, but how neural circuits encode naïve and learned olfactory preferences, and switch between those preferences, is poorly understood. Here, we map an olfactory network, from sensory input to motor output, which regulates the learned olfactory aversion of Caenorhabditis elegans for the smell of pathogenic bacteria. Naïve animals prefer smells of pathogens but animals trained with pathogens lose this attraction. We find that two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
279
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(298 citation statements)
references
References 50 publications
17
279
2
Order By: Relevance
“…5C). Previously we showed that training with PA14 did not alter sensory-evoked calcium responses in the AWB and AWC sensory neurons (17). These results suggest that aversive training reduces AVA calcium response.…”
Section: Dbl-1 Signals To the Hypodermis To Direct Aversive Olfactorymentioning
confidence: 59%
See 2 more Smart Citations
“…5C). Previously we showed that training with PA14 did not alter sensory-evoked calcium responses in the AWB and AWC sensory neurons (17). These results suggest that aversive training reduces AVA calcium response.…”
Section: Dbl-1 Signals To the Hypodermis To Direct Aversive Olfactorymentioning
confidence: 59%
“…For the promoters used in transgenic lines, we found no significant impact of their expression on learning using the corresponding fluorescent reporters and the transformation marker (Table S2). The aversive olfactory training and learning assays were performed similarly as previously described (16,17). For transgenic lines, the transgenic and nontransgenic siblings were trained on the same plates, their learning ability was measured in the same chemotaxis assays, and the results were scored by the experimenter before the genotypes were identified according to the expression of a fluorescent transformation maker in transgenic animals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6g,h). AWB are known to mediate avoidance of the repellent nonanone 12 and it was recently reported that AWB are activated after removal of nonanone 31 . We observed calcium increases in AWB after the removal of isoamyl alcohol, and similar to ASH, maximal responses were observed at 10 − 2 dilution, while considerable responses were not detected at 10 − 4 and 10 − 6 dilutions after the removal of isoamyl alcohol (Fig.…”
Section: Neural Responses Change Depending On Odour Concentrationsmentioning
confidence: 99%
“…Associative learning involves the modulation of a behavior to a conditioned stimulus (CS) by its predictive pairing with an unconditioned stimulus (US) (Levitan and Kaczmarek, 1991). Worms can pair the odorant diacetyl (CS) with aversive acetic acid (US) (Morrison et al, 1999), the smell of pathogenic bacteria (CS) with sickness (US) (Zhang et al, 2005;Ha et al, 2010), as well as a number of cues such as temperature (CS) (Hedgecock and Russell, 1975;Mori and Ohshima, 1995;Mohri et al, 2005), salt (CS) (Wen et al, 1997;Saeki et al, 2001), or odorants (CS) (Nuttley et al, 2002;Torayama et al, 2007) …”
Section: Introductionmentioning
confidence: 99%